Schwertmannite transformation via direct or indirect electron transfer by a sulfate reducing enrichment culture. (November 2018) - Zeng, Yufei; Wang, Han; Guo, Chuling; Wan, Jingjing; Fan, Cong; Reinfelder, John R.; Lu, Guining; Wu, Fengchang; Huang, Weilin; Dang, Zhi
Abstract: Understanding the mechanism of the microbial transformation of Fe(III)-oxyhydroxysulfate minerals is of considerable interest, because this transformation plays an important role in controlling the behaviour of toxic metals from acid mine drainage (AMD). In this study, we examined a sulfate reducing enrichment culture from AMD-contaminated sediments and predicted the possible pathway of electron transfer when incubated with schwertmannite, a common Fe(III)-oxyhydroxysulfate occurring in the AMD environment. Experiments were designed to distinguish the mechanisms by which bacteria facilitate direct (i.e., bacteria allowed to adhere to the mineral) or indirect (i.e., bacteria separated from the mineral by dialysis bag) electron transfer to reduce the mineral. The effects of adding anthraquinone-2, 6-disulfonate (AQDS) as an exogenous electron shuttle were also investigated. Vivianite was detected as the main product of schwertmannite transformation. Reduction of sulfate and iron were more pronounced in direct treatments, while more non-reductive dissolution were observed in indirect treatments. The addition of AQDS lead to the production of more dissolved Fe 2+ over 20 d than in the absence of AQDS. Microbial community composition differed in direct and indirect treatments, while the addition of AQDS did not significantly affect the community structure in each treatment. After incubation for 20 d, the growth of Desulfovibrio exceeded that of the originally dominant Citrobacter in direct treatments, while an unknown genus most closely related to Citrobacter within Enterobacteriaceae was predominant in indirect treatments. This monodominant community in indirect treatments was assumed not to transfer electron directly to schwertmannite but to rely on shuttling mechanism. PICRUSt results implied that bacteria in indirect treatment have potential to produce shuttling compounds or complexing agents. The absence of dsr genes and the putative fermentative process suggested that the Enterobacteriaceae might indirectly facilitate the dissolution and transformation of schwertmannite. Graphical abstract: Image 1 Highlights: The mineral transformation of schwertmannite by SRB enrichment was characterized. Indirect and direct electron transfers were both observed. Enterobacteriaceae play an important role in indirect electron transfer. Different patterns of functional profiles and sulfur metabolism genes were predicted.